The Cambridge companion to British theatre of the First World War - Brooks, Helen E. M. 1981-; Hammond, Michael 1954- (Cambridge companions to theatre and performance, 2023)
"This is the first comprehensive guide to British theatre's engagement with the First World War over the last century, from 1900 to the Armistice Day centenary in 2018. Considering theatre as both an industry and literary-cultural artform, it provides a contextual grounding in the prelude to the conflict and coverage of post-war plays as well as wartime performances. Lively chapters from leading scholars explore diverse genres and practices, from Shakespeare to melodrama, while focusing on topics including regionality, national identity, propaganda, commemoration, gender, censorship and international influences. Presenting original scholarship in an accessible and engaging manner, this Companion establishes theatre as a vital means of understanding wartime experiences, and a central feature in commemoration and remembrance."